2022
DOI: 10.3390/ijms23158151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of the G-Protein Genes and Their Expression Profiles in Response to Nitrogen Deprivation in Brassica napus

Abstract: Heterotrimeric guanine nucleotide binding protein (G-protein) consisting of Gα, Gβ, and Gγ subunits is one of the key signal transducers in plants. Recent studies indicated that G-protein has been proposed as an important mediator of nitrogen responses in rice, wheat, and Arabidopsis. However, little is known about these G-proteins in Brassica napus (B. napus), except for three identified G-proteins, BnGA1, BnGB1, and BnGG2. Therefore, the aim of the present study is to characterize the members of the G-protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Heterotrimeric guanine nucleotide binding proteins (G proteins) are crucial molecular switches for transmitting signal from G protein-coupled receptor (GPCR) to various downstream effectors [22] . The G proteins, composed of α, β, and γ subunits, are involved in a variety of BPs, including cell proliferation, inflammation, and immune response [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Heterotrimeric guanine nucleotide binding proteins (G proteins) are crucial molecular switches for transmitting signal from G protein-coupled receptor (GPCR) to various downstream effectors [22] . The G proteins, composed of α, β, and γ subunits, are involved in a variety of BPs, including cell proliferation, inflammation, and immune response [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In rice, WRKY33 (Os01g0826400) Os03g0609500 (LBD38), Os03g0445700 (LBD37), Os07g0589000 (LBD37), Os05g0114400 (ZOS5-02), Os11g0184900 (NAC5), Os07g0119300 (MYB), and Os03g0764600 (MYB) www.nature.com/scientificreports/ and CIPK14 are among the 34 N-sensitive genes 72 . The heterotrimeric guanine nucleotide binding protein (G-protein), has been suggested as a key modulator of N response in rice, wheat, and Arabidopsis 79 . TaNBP1 has been found to encode G proteins in wheat, which increase N uptake under N deficit conditions 80 .…”
Section: Discussionmentioning
confidence: 99%
“…WD40 proteins are involved in various processes, such as growth and development, metabolite biosynthesis, and immune and stress responses [ 13 , 21 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Furthermore, it has been shown in Arabidopsis [ 15 , 46 , 47 ], rice [ 29 , 48 , 49 , 50 ], maize [ 51 , 52 , 53 ], and rapeseed [ 54 , 55 ] that G-proteins are involved in abiotic stresses. In this study, the qRT-PCR analysis showed that the expression of TaGB1-B changed under stress and hormone treatments ( Figure 2 a–i).…”
Section: Discussionmentioning
confidence: 99%